2015
DOI: 10.1039/c4tc02688h
|View full text |Cite
|
Sign up to set email alerts
|

Chemical interaction and ligand exchange between a [(CH3)3Si]3Sb precursor and atomic layer deposited Sb2Te3films

Abstract: The chemical interaction between the [(CH 3 ) 3 Si] 3 Sb precursor and atomic layer deposited Sb 2 Te 3 thin films was examined at temperatures ranging from 70 to 220 C. The trimethylsilyl group [(CH 3 ) 3 Si] displays greater affinity for Te than for Sb, and this drives replacement of Te in the film with Sb from the [(CH 3 ) 3 Si] 3 Sb precursor, while eliminating volatile [(CH 3 ) 3 Si] 2 Te, especially at elevated temperatures. The compositions of the resulting Sb-Te layers lie on the Sb 2 Te 3 -Sb tie line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Even when the SS subcycle number increases further, no further decrease in the GR of Te was observed since the film surface is now covered with Sb and outward diffusion of Te at this temperature is not active. 21 From the slope of the best linear fitted graph of GR of Sb, the incorporated amount of Sb per SS subcycle, which could be ascribed exclusively to the ligand exchange reaction, was 41.6 ng·cm −2 ·subcycle −1 . Since two Sb-precursor pulse steps (Sb(OC 2 H 5 ) 3 and [(CH 3 ) 3 Si] 3 Sb) were involved in one SS subcycle, the average increase in GR of Sb per Sb-precursor pulse is 20.8 ng·cm −2 · subcycle −1 .…”
Section: Chemistry Of Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even when the SS subcycle number increases further, no further decrease in the GR of Te was observed since the film surface is now covered with Sb and outward diffusion of Te at this temperature is not active. 21 From the slope of the best linear fitted graph of GR of Sb, the incorporated amount of Sb per SS subcycle, which could be ascribed exclusively to the ligand exchange reaction, was 41.6 ng·cm −2 ·subcycle −1 . Since two Sb-precursor pulse steps (Sb(OC 2 H 5 ) 3 and [(CH 3 ) 3 Si] 3 Sb) were involved in one SS subcycle, the average increase in GR of Sb per Sb-precursor pulse is 20.8 ng·cm −2 · subcycle −1 .…”
Section: Chemistry Of Materialsmentioning
confidence: 99%
“…21 It has been reported that the [(CH 3 ) 3 Si] 3 Sb precursor pulsed on a previously grown Sb 2 Te 3 layer reacts with the film forming the volatile [(CH 3 ) 3 Si] 2 Te and elemental Sb as the reaction products. 21 In addition, it was also found that Sb(OC 2 H 5 ) 3 and [(CH 3 ) 3 Si] 3 Sb react with each other resulting in elemental Sb in an ALD manner via a reaction similar to that between Sb(OC 2 H 5 ) 3 and [(CH 3 ) 3 Si] 2 Te. So this method can also be used to grow Sb-rich Sb−Te films.…”
Section: Introductionmentioning
confidence: 99%
“…So far, various techniques have been reported capable of Sb 2 Te 3 deposition, including microwave-assisted solvothermal synthesis, 16 sputtering, 17,18 chemical vapor deposition, 19,20 atomic layer deposition, 12,[21][22][23][24][25][26] molecular beam epitaxy, [27][28][29][30] and Metal-Organic Chemical Vapor Deposition (MOCVD). [31][32][33][34][35][36][37][38][39] Amongst these methods, MOCVD, an industrially ready technique historically adopted for large-scale semiconductor production and suitable for large area lm growth, appears to be the preferred scale-up option in an industrial environment.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, our methodology exploits the reaction family concept where the reactive center of transition states of a given reaction family (e.g., ammonia elimination or hydrogenation) is assumed to be conserved, and pre-exponential factors and activation energies vary proportionally to the substitutions on this reactive center. Model compounds, or small molecules that have one or few reactive features that are proposed to have analogous reactivity to substructures present in larger nitriles, have been studied previously in our group. To capture the liquid-phase effects of the experimental reactor conditions, we consider ideal liquid behavior in our reactor model as a first approximation. Details for our isothermal reactor model development are explained below, including definitions of key rate expressions, pseudo-steady-state approximations, nitrile conversion, and selectivity toward higher amines.…”
Section: Computational Methodologymentioning
confidence: 99%